(untitled) (Research, Society and Development, 2023)
Objective: To identify the profile of nursing students from a private institution in Salvador located in the state of Bahia. Method: Quantitative research, developed through the umbrella project of scientific initiation of a Private Institution, entitled "Perception of nursing students on leadership in professional practice", approved by the ethics committee under opinion No. 4,532,794, held between from April to June 2021, whose focus was to analyze data from nursing undergraduates from a private institution in the fifth and tenth semester through the Google Forms platform. Results: 22 academics between the 5th and 10th semester contributed to this study, after analyzing the data, it was possible to identify the predominance of a female audience, black, with an average age between 21 and 30 years, most of them called themselves black race/color, heterosexual and single with income between 1 and 3 minimum wages. Conclusion: The study shows a predominance of females, aged between 21 and 30 years, young, single, heterosexual, who call themselves black, with family income between 1 and 3 minimum wages. It is noteworthy that the study characterizes the profile of students from a private institution, making it possible to map and outline effective strategies that meet the demands and needs of its public.